No differences between 4‐strand semitendinosus or semitendinosus/gracilis grafts in revision rates, knee stability and patient‐reported outcomes after primary anterior cruciate ligament reconstruction - Torsten Grønbech Nielsen; Martin Lind (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose The purpose of this study was to compare revision rates, knee stability and patient‐reported outcomes in a national cohort of anterior cruciate ligament (ACL) reconstructed patients using either the semitendinosus/gracilis (ST/G) or the 4‐strand semitendinosus (4‐ST) grafts. Methods ACL reconstructed patients operated from 2015 to 2021 who met the following criteria: minimum 2‐year follow‐up and isolated ACL with either ST/G or 4‐ST grafts. The primary outcome was ACL revision surgery assessed at 2‐year follow‐up. Secondary outcomes were knee laxity (side‐to‐side difference) and pivot shift (rotational stability difference—Grade 0 or Grade 1–3), and patient‐reported outcomes; Knee Osteoarthritis and Outcome Score (KOOS) subscales and Tegner activity scale assessed at 1‐year follow‐up. Results A total of 6750 ST/G and 1321 4‐ST patients were included in the study. There was no statistical difference in 2‐year revision rates between the groups (ST/G; 1.73 (95% confidence interval [CI] 1.44–2.07), 4‐ST; 1.40 (95%CI 0.88–2.21)). A small significant but not clinically relevant difference was seen in knee laxity (1.27 mm vs. 1.13 mm), but no other significant differences were seen in pivot shift or patient‐reported outcomes at one year. Both groups showed significant improvement from baseline to 1 year. Conclusion The present study found no difference between ST/G or 4‐ST in ACL reconstruction patients regarding revision rates, knee laxity and patient‐reported outcomes. Level of Evidence Level III.